Exploratory study on the effectiveness of integrative neurocognitive remediation therapy (iNCRT) for cancer survivors. (1st June 2022) - Rogiers, A.; Kyndt, D.; Van Eycken, S.; Le Febvre, J.-C.; Brohee, M.; Degols, C.; Fontaine, C.; Neyns, B.; Kornreich, C.
Abstract : Introduction: Cancer survivors frequently report suffering from neurocognitive impairment, that persists after physical recovery from their disease. Cognitive impairment is associated with important emotional disturbances, socio-professional consequences and diminished quality of life. Objectives: This observational study aims to assess the effectives of an integrative neurocognitive remediation therapy (iNRCT), offered as a 12-week program (1day/week), organized within our Cognitive Remediation Clinic. The iNCRT combines personalized computerized cognitive training and neurocognitive strategy training, with group sessions of physical exercise, mindfulness, and cognitive behavior therapy (CBT). Methods: The assessment before and after NCRT includes neuropsychological testing (10 subtests), assessment of daily functioning and subjective neurocognitive function (NCF). Results: Out of 16 eligible cancer survivors, 12 patients were recruited and 11 completed the iNCRT; median age 53 years [range, 41-71]; 3 patients had a prior history of a central nervous system tumor, 5 patients of breast cancer, 2 patients of stage-IV melanoma, and 1 patient of gastric cancer. After iNCRT subjective NCF did not improve significantly (p=0.13) according to the Cognitive Failure Questionnaire. However neuropsychological assessment revealed an improvement on ≥ 1 impaired subtest in all patients; 6 patients improved on ≥ 4 impaired subtests. Improvement was most prominent in long-term verbal and visual memory, working memory and executive function. All patients reported a clinical benefit in their daily function after completion of iNCRT. Conclusions: Our iNRCT, which combines personalized neurocognitive training with physical exercise, mindfulness and CBT can be an effective therapeutic model for treating neurocognitive impairment in cancer survivors, with a clinically relevant impact on their daily function. Disclosure: No significant relationships.